2013
DOI: 10.1002/elps.201370051
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of protein electrophoresis in silica colloidal crystals having brush layers of polyacrylamide

Abstract: Sieving of proteins in silica colloidal crystals of mm dimensions is characterized for particle diameters of nominally 350 and 500 nm, where the colloidal crystals are chemically modified with a brush layer of polyacrylamide. A model is developed that relates the reduced electrophoretic mobility to the experimentally measurable porosity. The model fits the data with no adjustable parameters for the case of silica colloidal crystals packed in capillaries, for which independent measurements of the pore radii wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…With the colloidal nanoparticle array, migration occurred in the order of increasing molecular mass, consistent with sieving. The apparent linear dependence of ln μ on molecular mass (Figure 3B) is consistent with free‐volume (Ogston) sieving models [12,17,25,26,45–47]. The model assumes that the ratio of electrophoretic mobility, μ , to the mobility in free solution μ 0 is equal to the fraction f of the total volume in a porous medium that can be occupied by the analyte during migration, given by [46–48]: μμ0=f=eKC…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…With the colloidal nanoparticle array, migration occurred in the order of increasing molecular mass, consistent with sieving. The apparent linear dependence of ln μ on molecular mass (Figure 3B) is consistent with free‐volume (Ogston) sieving models [12,17,25,26,45–47]. The model assumes that the ratio of electrophoretic mobility, μ , to the mobility in free solution μ 0 is equal to the fraction f of the total volume in a porous medium that can be occupied by the analyte during migration, given by [46–48]: μμ0=f=eKC…”
Section: Discussionsupporting
confidence: 69%
“…Silica colloidal crystal arrays afford an alternative separation mechanism in microdevices [1,12]. The colloidal array was formed in the separation channel of a PDMS chip with a glass base [1,12,25,26]. PDMS/glass chips were cast with wide channels (∼100 μm) from a mold with a thick PDMS layer (∼5 mm), resulting in relatively deep reservoirs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, applications of CCs have noticeably increased in many fields; however, to date, this quote still applies to the field of separation science. Only few studies have reported the application of CCs as the media for microfluidic and chromatographic separation either in planar forms or as packed, short microcapillaries (length ≤ 5 cm). …”
Section: Introductionmentioning
confidence: 99%